Green Marketing: An Illusion or Reality - Jain, Sheenu (Indian Journal of Marketing, 2007)
What has happened to "Green Marketing [1]"? In these early years of the new millennium, it is now some 20 years on from the Brundtland Report and the "euphoric" discovery of the environment by marketing practitioners and academics. Over those years, we have seen much research, many product launches and campaigns, and many books, papers and conferences. Despite all this, green marketing gives the impression of having significantly underachieved. Even to the most casual observer, the 1990s largely disappointed in their billing as the decade that would precipitate a "green revolution" in marketing. That decade began with eminently hopeful forecasts about the emergence of a "green tide" (Vandermerwe and Oliff, 1990) of consumers and new products. Yet, this has clearly not materialized as expected. Instead, consumers have become disillusioned; many of the groundbreaking green products produced by specialist firms have left the market; the dramatic growth in green product introductions at the beginning of the 1990s has subsided; and companies have become cautious about launching environmentally-based communications campaigns for fear of being accused of "green washing".